P162 Prevalence of nafld (non alcoholic fatty liver disease) and fibrosis in inflammatory bowel disease: the impact of traditional risk factors, intestinal inflammation and genetic phenotype. (15th January 2020) - Scrivo, B; Celsa, C; Busacca, A; Giuffrida, E; Pipitone, R M; Grimaudo, S; Calogero, C; Petta, S; Cappello, M
Abstract: Background: Prevalence of NAFLD has recently been reported increased in inflammatory bowel disease (IBD) with conflicting results due to heterogeneity of published studies, especially in the diagnostic definition of NAFLD. The increased risk of NAFLD might be related to traditional risk factors but also to IBD-related factors. The role of genetic markers has been addressed only in one study. The aim of our study has been to assess the prevalence of NAFLD and fibrosis in a homogeneous cohort of patients with IBD, assessing the role of metabolic, disease-related and genetic factors. Methods: the diagnosis of NAFLD was based on transient fibroelastometry findings (CAP ≥288 dB/m) and HSI (Hepatic Steatosis Index). Demographic data, traditional risk factors for NAFLD ( BMI, lipid profile), comorbities, laboratory tests, disease features (type of IBD, duration, extent, extraintestinal manifestations, relapses/year, disease activity, previous surgery, therapy) were registered in a dedicated database. PNPLA3 rs738409 C>G single nucleotide polymorphism, encoding for I148M protein variant, was investigated by Taqman assay. Results: 208 consecutive patients were enrolled: 120 males, 121 Crohn's disease, 87 ulcerative colitis, mean age 46, 4 ± 15, 2 years. 26 patients (12, 5%) were on steroids, 121 on biologics. The prevalence of NAFLD was 20, 7% with mean HSI being 38, 3 ± 4, 7.On univariate analysis, patients with NAFLD were older (54, 6 ± 11, 1 years), had higher BMI (28, 1 ± 3, 9 vs. 24, 1 ± 3, 8), had more frequently hypertension and high level of LDL and tryglicerides. No significant difference was found as far as concerns gender, number of relapses, extraintestinal manifestations, disease activity and duration and ongoing therapy. Medium stiffness value was higher in patients with NAFLD (6, 4 ± 2, 4 vs. 4, 8 ± 2, 2 KPa). CG phenotype of PNAPL3 was more frequent among NAFLD patients, though the result was not significant. On multivariate analysis age, BMI, previous surgery and level of stiffness > 6, 9 kPa were independently related to NAFLD. Conclusion: This single center cross-sectional study shows that, by using transient elastography, the prevalence of NAFLD in IBD is 20, 7% with a significantly increase of liver stiffness and development of fibrosis. NAFLD was related to traditional risk factors (age, BMI, lipid profile) and to previous ileal resection, the last probably due to changes of gut microbiota. Neither intestinal inflammation and drugs nor genetic testing for PNAPL3 seem to be related to the development of NAFLD. Longitudinal studies are warranted to assess the progression of fibrosis and the role of therapeutic interventions.